2015
DOI: 10.1017/s1755691016000190
|View full text |Cite
|
Sign up to set email alerts
|

Mandible morphology and diet of the South American extinct metatherian predators (Mammalia, Metatheria, Sparassodonta)

Abstract: Sparassodonta is a diverse group of extinct metatherian predators that include forms with diets ranging from omnivores to hypercarnivores, including potential bone-crushers and sabre-tooth specialised species. Most of the previous dietary studies on the group were based on qualitative approaches or dental morphometric indexes and/or bite force estimations. In this study, we explore the evolution of mandible shape and diet of Sparassodonta in a comparative phylogenetic framework, using geometric morphometric to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 77 publications
3
18
0
Order By: Relevance
“…The results also further confirmed that skull shape were affected by phylogeny (Table 3). Our results were consistent with those of previous studies [50][51][52], which confirmed that the morphology of the cranium or mandible are affected and restricted by phylogeny in birds and mammals.…”
Section: Differences In Skull Morphology Among Speciessupporting
confidence: 93%
“…The results also further confirmed that skull shape were affected by phylogeny (Table 3). Our results were consistent with those of previous studies [50][51][52], which confirmed that the morphology of the cranium or mandible are affected and restricted by phylogeny in birds and mammals.…”
Section: Differences In Skull Morphology Among Speciessupporting
confidence: 93%
“…Dietary Hasirts: Several features suggest that borhyaenids and non-thylacosmiline proborhyaenids used p3, the largest and most robust premolar in all sparassodonts, to crack bones. These include an interlocking or fused mandibular symphysis, deep dentary, bulbous premolars (especially P/p3) with long roots, enamel microfractures, and high estimated bite force (Blanco et al, 2011;Ercoli et al, 2014;Forasiepi et al, 2015;Echarri et al, 2017). Contrary to a possible first impression of this robust-skulled new taxon, Eomakhaira does not seem to have been specialized for bone cracking (sensu Werdelin, 1989), Preyious authors have noted that mandible depth in bone-cracking carnivorous mammals is often that same below the primary carnassial and the bone-cracking premolar, resulting in the ventral border of the horizontal ramus of the dentary to appear straight in lateral view (Palmqvist et al, 2011;Forasiepi et al, 2015).…”
Section: Discussion Paleobiology Of Sgopv 3490mentioning
confidence: 99%
“…In sparassodonts, a deep mandible with a straight ventral border and roughly uniform depth between p3 and m4 occurs in Australohyaena, Proborhyaena, Paraborhyaena, and Arctodictis, and these taxa have all been considered to be bone-crackers (Blanco et al, 2011;Ercoli et al, 2014;Forasiepi et al, 2015;Echarri et al, 2017). By contrast, the dentary is much shallower under p3 than under m4 in Eomakhaira, and the ventral border of the mandible is curved in lateral view.…”
Section: Discussion Paleobiology Of Sgopv 3490mentioning
confidence: 99%
“…[ 64 ]), but recent studies using stable isotopes and dental wear have demonstrated that a simple relationship between hypsodonty and diet does not hold for this group [ 65 , 66 ], despite its use for many other clades. Studies of mandible shape in sparassodonts have interpreted some species as more omnivorous (mesocarnivorous or hypocarnivorous) than suggested by their dentition [ 20 , 67 ], and this could reflect inaccuracies in interpreting sparassodont dental ecomorphology based on metrics derived from modern carnivorans. Interestingly, Marshall's [ 10 ] qualitative analysis of sparassodonts envisaged much greater dietary breadth in the group, with three Santa Cruz genera classified as large carnivores ( Acrocyon , Arctodictis , Borhyaena ), two as large omnivores ( Lycopsis , Prothylacynus ), and the remainder as small to medium carnivores or omnivores similar to modern mustelids, mephitids, canids and didelphids (see his fig.…”
Section: Discussionmentioning
confidence: 99%